Evaluation of Satisfaction of Adolescents Treated by Dental Students - Carolina Reis Fernandes Coelho; Fernanda Ribeiro Pedrosa; Lívia Guimarães Zina; Flávio de Freitas Mattos; Renata de Castro Martins; João Henrique Lara do Amaral; Andrea Clemente Palmier; Mara Vasconcelos (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the satisfaction of adolescents undergoing dental treatment between 2016 and 2018 at the Dental School of the Federal University of Minas Gerais (FAO UFMG). Material and Methods: A descriptive cross-sectional study using the Oral Health Services Satisfaction Assessment Questionnaire (QASSaB). The structured questionnaire has eleven questions divided among the dimensions: dentist / patient relationship, relationship with other professionals, effectiveness, accessibility/availability, technical-scientific quality, cleanliness and physical environment, acceptability, effectiveness/resolution, each with five response options. Descriptive data analysis was performed using absolute and relative frequencies. Results: A total of 145 adolescents participated in this study, 60 males and 85 females; 74.85% of adolescents rated dental treatment received as excellent, 76.7% reported having no symptoms after treatment, 46.2% considered it easy/very easy to get treatment, 65.6% reported that waiting time was short/very short, 90% considered dental equipment modern/very modern, 98% regarded the cleanliness of the waiting room and bathrooms as being excellent, 83.4% reported that they always received an explanation about the treatment, and 51.57% were totally satisfied with the appearance of the treated teeth and their chewing capacity. Conclusion: It was possible to observe that the adolescents, users of FAO UFMG, were satisfied with the service in the studied dimensions: human relations, effectiveness, accessibility/availability, technical-scientific quality, physical environment/cleanliness, acceptability and resolvability/effectiveness.